Systematic Review on Information Technology Approaches to Evaluate the Impact of Public Health Campaigns: Real Cases and Possible Directions - Pinto, Rafael; Silva, Lyrene; Valentim, Ricardo; Kumar, Vivekanandan; Gusmão, Cristine; Oliveira, Carlos Alberto; Lacerda, Juciano (Frontiers in Public Health, 2022)
Evaluating the success of a public health campaign is critical. It helps policy makers to improve prevention strategies and close existing gaps. For instance, Brazil's “Syphilis No!” campaign reached many people, but how do we analyze its real impact on population awareness? Are epidemiologic variables sufficient? This study examined literature on using of information technology approaches to analyze the impact of public health campaigns. We began the systematic review with 276 papers and narrowed it down to 17, which analyzed campaigns. In addition to epidemiological variables, other types of variables of interest included: level of (i) access to the campaign website, (ii) subject knowledge and awareness, based on questionnaires, (iii) target population's interest, measured from both online search engine and engagement with Social Network Service, and (iv) campaign exposure through advertising, using data from television commercials. Furthermore, we evaluated the impact by considering several dimensions such as: communication, epidemiology, and policy enforcement. Our findings provide researchers with an overview of various dimensions, and variables-of-interest, for measuring public campaign impact, and examples of how and which campaigns have used them.